Door Security Design Using Fingerprint and Buzzer Alarm Based on Arduino - Mario Junianto Manurung; Poningsih Poningsih; Sundari Retno Andani; Muhammad Safii; Irawan Irawan (Information Technology and Science (ITScience), 2021)
The level of crime of theft in people's homes from time to time is increasing and increasingly unsettling for many people and various groups, from leading sources claiming that there has been an increase in theft in people's homes from the previous year, by conducting research objects in the community by identifying existing problems. It can be concluded that this happens because the house door security system still uses conventional which is classified as unsafe or easily broken into, by carrying out research method steps in the form of analysis and data collection and in the form of designing tools by describing some of the main supporting tools that the problem can be minimized by using technology that is currently developing that is already well systemized, namely using a microcontroller or Arduino as the main control center, assisted by using a fingerprint sensor as a process for recording and identifying fingerprints and NodeMCU for to connect to a WiFI network where later on that the door can also be controlled using android via a wifi network as a remote control and an alarm buzzer which will function if when the fingerprint identification process fails, the alarm will sound as a warning sign, it will be concluded to design a door safety device using arduino based fingerprint and alarm buzzer for better system. Which only fingers that have been registered and registered android can open the door. This research is expected to be able to optimize door security in people's homes to avoid crimes such as thieves.